(untitled) (ModaPalavra e-periódico, 2012)
The different types of fashion design used for the garment industry, even if intrinsically linked and interrelated, because they have elements of connection between them, still generate confusion in the teaching and learning for fashion drawing to projectable idealization. Why have specific characteristics, the design keeps changing depending on the stage at which it is used by the designer in the process of trajectory of idealization planning.